(untitled) (Journal of Medicine, 2018)
Vertigo can be central or peripheral causes. However, determining the cause can be difficult as central vertigo may mimic the presentation of peripheral vertigo. Hence, we report three cases of central vertigo, to highlight the importance of early recognition and clinical suspicions in managing the aforementioned cases which may present with debilitating daily living. J MEDICINE JUL 2018; 19 (2) : 126-129